Application of an ontology for model cards to generate computable artifacts for linking machine learning information from biomedical research - Amith, Muhammad Tuan; Cui, Licong; Roberts, Kirk; Tao, Cui (Proceedings of the ... International World-Wide Web Conference. International WWW Conference, 2023)
Model card reports provide a transparent description of machine learning models which includes information about their evaluation, limitations, intended use, etc. Federal health agencies have expressed an interest in model cards report for research studies using machine-learning based AI. Previously, we have developed an ontology model for model card reports to structure and formalize these reports. In this paper, we demonstrate a Java-based library (OWL API, FaCT++) that leverages our ontology to publish computable model card reports. We discuss future directions and other use cases that highlight applicability and feasibility of ontology-driven systems to support FAIR challenges.